Improving the Low Gear in Volleyball (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the organization of the educational and training process in volleyball. The concept of lower gear technique is considered. Recommendations are given on the construction of a lesson, for training and improving the lower gear among students of the elective group in volleyball at Petrozavodsk State University.